2021
DOI: 10.1609/aiide.v13i1.12939
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Goal Recognition in Open-World Digital Games

Abstract: Recent years have seen a growing interest in player modeling to create player-adaptive digital games. As a core player-modeling task, goal recognition aims to recognize players’ latent, high-level intentions in a non-invasive fashion to deliver goal-driven, tailored game experiences. This paper reports on an investigation of multimodal data streams that provide rich evidence about players’ goals. Two data streams, game event traces and player gaze traces, are utilized to devise goal recognition models from a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…LSTMs are broadly effective at handling noisy, probabilistic data. Prior work on player goal recognition in open-world games has found that LSTMs outperform several non-LSTM baselines (e.g., nonrecurrent deep neural networks, conditional random fields, Markov logic networks, n-grams) across a range of evaluation metrics (Min et al 2016, Min et al 2017. We extend this work by formalizing player plan recognition in terms of two complimentary prediction tasks: (1) goal recognition of high-level player goals and (2) action sequence recognition of low-level actions players enact in the game environment.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…LSTMs are broadly effective at handling noisy, probabilistic data. Prior work on player goal recognition in open-world games has found that LSTMs outperform several non-LSTM baselines (e.g., nonrecurrent deep neural networks, conditional random fields, Markov logic networks, n-grams) across a range of evaluation metrics (Min et al 2016, Min et al 2017. We extend this work by formalizing player plan recognition in terms of two complimentary prediction tasks: (1) goal recognition of high-level player goals and (2) action sequence recognition of low-level actions players enact in the game environment.…”
Section: Related Workmentioning
confidence: 99%
“…Once event sequences were segmented by planning support tool use, we created a vector representation of these sequences using one-hot encoding vectors. These steps have been shown in prior work to be the most effective for goal recognition tasks (Goslen, et al 2022;Min et al, 2017). There were 385 event sequences after processing the data across all players.…”
Section: Framework Inputmentioning
confidence: 99%
“…• Block #4 -Estimated Player Policy: To increase the reliability of an available rollout function, the manager might use an estimated player policy to estimate which action(s) the player might perform next, given their prior gameplay history. An example of this block can be found in a study by Min et al (2016), where they attempted to model how players would form and pursue new goals based on their prior experiences in the game. • Block #5 -Feature Vector: Given a trajectory of a player's prior (or potential future) experience in the game, it is common for managers to extract higher-level information that can aid in their reasoning process.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Prior work has explored the use of traditional machine learning algorithms with handcrafted features to address this (Ha et al, 2011;Mott et al, 2006). Recent work using deep learning methods has eliminated the need for feature engineering and allowed for more generalizable methods (Min et al, 2014;Min et al, 2016b;Min et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to low-level gameplay actions, other modalities such as eye gaze data (Min et al, 2017b) have been investigated to improve the performance of goal recognition models by leveraging an expanded set of predictive features that may also indicate player goals. Another source of evidence that may support improved goal recognition in openworld games is students' natural language, written reflections during and after gameplay.…”
Section: Introductionmentioning
confidence: 99%